Alternative Readings of J. M. Synge’s Drama Predicated on Archival Material - Kurdi, Mária (Hungarian Journal of English and American Studies, 2020)
Book review: Collins, Christopher. Theatre and Residual Culture: J. M. Synge and Pre-Christian Ireland. London: Palgrave Macmillan, 2016. 301 pages. Hb. ISBN 978-1-349-94871-0. €106.99.